The Practice of Hegemony Toward Child Soldier in “Beast of No Nation” by Uzodinma Iweala - Angie Kristiawan, Yohanes; Adhitya, Galant Nanta; Hapsari, Apriliana ((JELE) Journal Of English Language and Education, 2024)
This paper tries to uncover the practice of hegemony that is experienced by the child soldier. The research will be done by using data from the novel as the main source and supported by the related theories in order to provide well-covered explanation and discussion. This paper uses qualitative research methodology as a systematic strategy. The main focus of this paper is to explore the looking of finding on how the practice is portrayed and displayed. The results show that the leader, Commandant has been practicing a successful hegemony among the children. The child soldier’s behavior and attitude are also changed. These innocent children turned into a bunch of cruel and inhumane individuals and would always obey Commandant's orders.